Upscaling of lignin precursor melt spinning by bicomponent spinning and its use for carbon fibre production. (1st November 2021) - Bostan, Lars; Hosseinaei, Omid; Fourné, Renate; Herrmann, Axel S.
Abstract : Upscaling lignin-based precursor fibre production is an essential step in developing bio-based carbon fibre from renewable feedstock. The main challenge in upscaling of lignin fibre production by melt spinning is its melt behaviour and rheological properties, which differ from common synthetic polymers used in melt spinning. Here, a new approach in melt spinning of lignin, using a spin carrier system for producing bicomponent fibres, has been introduced. An ethanol extracted lignin fraction from LignoBoost process of commercial softwood kraft black liquor was used as feedstock. After additional heat treatment, melt spinning was performed in a pilot-scale spinning unit. For the first time, biodegradable polyvinyl alcohol (PVA) was used as a spin carrier to enable the spinning of lignin by improving the required melt strength. PVA-sheath/lignin-core bicomponent fibres were manufactured. Afterwards, PVA was dissolved by washing with water. Pure lignin fibres were stabilized and carbonized, and tensile properties were measured. The measured properties, tensile modulus of 81.1 ± 3.1 GPa and tensile strength of 1039 ± 197 MPa, are higher than the majority of lignin-based carbon fibres reported in the literature. This new approach can significantly improve the melt spinning of lignin and solve problems related to poor spinnability of lignin and results in the production of high-quality lignin-based carbon fibres. This article is part of the theme issue 'Bio-derived and bioinspired sustainable advanced materials for emerging technologies (part 2)'.